Changes in surface icing duration over north China during 1961–2015. (2nd August 2018) - Yu, Yu; Ren, Zhihua; Gao, Feng; Meng, Xiaoyan
Abstract : Climate extremes are changing at mid–high latitudes due to the effects of climate change. We defined the duration of surface icing (ice formation on open water) in north China from 1961 to 2015, along with its annual start and end date, based on daily measurements by observers at 346 weather stations. A comprehensive analysis of the temporal and spatial variations in these data showed that the regional mean of annual surface icing duration has a high correlation coefficient of 0.97 with the number of frost days (calculated from the daily minimum temperature below 0 °C), with some discrepancies. As the start date trended later and the end date trended earlier in this region, the surface icing duration decreased by 2.6 days/decade from 1961 to 2015 and the slope became steeper by −4.8 days/decade during the most recent 25 years. These results contribute to a better understanding of changes in climatic extremes related to global climate change. Abstract : The influence of climate change in north China (north of latitude 35° N) was demonstrated from a unique perspective of changes in surface icing duration (SID). Since the start date of icing is postponed and the end date is brought forward, the SID in north China over the past 55 years shows a remarkable negative trend of −2.6 days per decade, while the greatest descending slope with −4.8 days/decade occurred in the recent 25 years from 1991–2015.